Actions Towards Academic Literacy Present inUndergraduate Course Descriptions of the State University of Parana - Ana Paula Trevisani; Francini Percinoto Poliseli Corrêa; Alessandra Silva Quadros Zamboni (Signum: Estudos da Linguagem, 2021)
In the context of internationalization and in different areas of knowledge, the generation and dissemination of scientific knowledge to promote citizenship, democracy, cultural diversity, human and sustainable development, at the local and global level, are intrinsically related to academic literacies in additional languages. Understanding academic literacies as the necessary skills that need to be developed to act in the academic context (LEA; STREET, 1998), this article presents the mapping of initiatives referring to academic literacies actions in English language, as perceived in course descriptions from the State University of Paraná (UNESPAR). The theoretical framework is the categorization of literacy models presented by Lea and Street (1998). This research is based on the mixed methods research (TASHAKKORI; CRESWELL, 2007), with interpretive, deductive and inductive analysis procedures, considering particularities of their context. Data were collected through 1) searching for course descriptions as they appear in Course Projects of Unespar; 2) analyzing descriptions in relation to terms associated with the categorization of literacy models (LEA; STREET, 1998; 2014). The analyses revealed few literacy actions focused on the English language, which indicate the need for institutionalized projects that meet the demands of academic literacies in that language.